The Center for Creative Leadership handbook of leadership development - Moxley, Russ S. 1944-; McCauley, Cynthia D. (Cynthia Denise) 1958-; Van Velsor, Ellen (A joint publication of Jossey-Bass business & management series and the Centor for Creative Leadership, 1998)
The Center for Creative Leadership is the world's largest institution devoted to leadership research and education. In this handbook over a dozen talented professionals join forces to outline the Center's philosophy and strategies. They present six proven methods of leadership development and illustrate how those methods have been successfully used in the real world. They give organizations a systemic approach and a means for evaluating the impact of their initiatives. And they pragmatically address such urgent topics as leadership growth for women and people of color, cross-cultural leadership development, and the development of global leaders.